A Study of the Problems of Wholesale Vegetable Marketing in Tripoli (L.A.R.) - NAWAS, FARID; CHAUDHRY, SHARIF; ASOWANI, M. (The Libyan Journal of Agriculture, 2023)
This marketing study was conducted in June 1973 at Thalatha market with the prime objective of identifying and finding out feasible solutions for the major problems facing farmers as well as commission agents in the wholesale disposal of vegetables. It was found out that the majority of middlemen prefer to deal with farmers on a commission basis since the method is popular and well-known to the concerned parties. The study also showed that the commission which middlemen receive for their services ranged from 3-9%, depending upon the varieties of vegetables, quantities sold, and other factors. A daily surplus of unsold vegetables, which besides lowering the price to the farmers creates further problems in the disposal of this surplus in the retail market, was also revealed by the study. Grading of vegetables has an increasing effect on the prices which farmers receive, the urgent need for reconsideration of the price control measures in such a way as to guarantee that consumers are getting good quality products at low prices; the impracticability of specialization in the marketing of vegetables middlemen, these and other results were fully presented and discussed in this paper.